Ewolucja ładu światowego w okresie pozimnowojennym (zarys problemu) - Okraska, Tomasz (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Evolution of post-Cold War international order (outline of the problem) The article is devoted to transformation of international order after the collapse of the bipolar system, given the major Cold War antecedents. Author analyzes the situation created after the collapse of the Soviet Union, pointing to the dominant role of the United States until the invasion of Iraq in 2003 and subsequent financial crisis. At the same time are discussed the factors affecting the potential of other countries, with particular emphasis on the increasing role of China and India. Author also examines the role of non-state actors in the contemporary world, being especially interested in importance of the international organizations and transnational corporations. Analyzed is also hostile use of ICT as a new treat to international security. Author draws attention to the phenomenon of displacement and diffusion of power in the postCold War world, which determine for all the countries need for action on multilateral basis. Key words: transformation, international order, bipolar system, displacement and diffusion of power